Electroacupuncture on Hemifacial Spasm and Temporomandibular Joint Pain Co-Morbidity: A Case Report - Huang, Jian-peng; Liang, Zhan-mou; Zou, Qi-wen; Zhan, Jie; Li, Wen-ting; Li, Sheng; Li, Kai; Fu, Wen-bin; Liu, Jian-hua (Frontiers in Neurology, 2022)
Background: Hemifacial spasm (HFS) and temporomandibular joint (TMJ) pain are common facial diseases, which cause depression, anxiety, insomnia, and poor quality of life. However, currently there is still no effective therapies to treat HFS and TMJ. Case presentation: We reported a case of a 50-year-old woman who presented with irregular spasm of eyelids and facial muscles on the left side, and the TMJ pain on the right side. She had been treated with carbamazepine (20mg per day) and alternative therapies for a year, but still not much improvement in the symptoms. Her scores of Jankovic Rating Scale (JRS), global rating scale (GRS), and visual analogue scale (VAS) was 7, 60, and 7 points, respectively. EMG test showed that the spastic side had higher R1 amplitude, longer R2 duration, and larger R2 area than the non-spasmodic side, and the occurrence rate of the lateral spread responses (LSR) in the Orbicularis oris and the Orbicularis oculi muscle was 60% and 40%, respectively. We considered this patient had left HFS and right TMJ pain. EA was successfully undertaken for two periods over 30 weeks. After EA, the JRS and VAS reduced sharply, and the symptoms of HFS were stable without recurrence. However, the frequency of lower eyelid increased gradually at 6-month follow-up. Conclusions: EA with the frequency of 2Hz and intensity of approximately 1-2 mA may be benefit for alleviating symptoms of HFS and TMJ pain without adverse reaction. The potential mechanisms of EA on HFS and TMJ pain co-morbidity involved brain stem mechanism for distal acupuncture and DNIC mechanism for local acupuncture analgesia.